Combination of hydrologic and hydraulic modeling on flood and inundation warning: case study at Tra Khuc-Ve River basin in Vietnam - Thai, Tran Hong; Tri, Doan Quang (Vietnam Journal of Earth Sciences, 2019)
Flooding caused by historically high flows, especially in Tra Khuc-Ve River basin in the Mid-Central region in Vietnam in November 2013, which caused widespread damage. The purpose of this paper was to establish the inundation maps in the downstream part of Tra Khuc-Ve rivers by using the coupling of the hydrological and hydraulic models (MIKE SHE/MIKE 11 and MIKE 11 GIS). Calibration and validation of the hydrological model were in good agreement in terms of the vibration amplitude, absolute value, and phases. The hydraulic model results showed good agreement between observed and simulated flood events in 2012 and 2013 after calibration and validation. The rainfall forecasting from the IFS model was also used to establish six flood warning scenarios based on the alarm level III (6.5 m) and the historical level (8.76 m). The inundation maps showed the extent of flooding and the water depth in the downstream part of the study area. The simulation results of historical data showed that Tu Nghia and Son Tinh Districts were the most affected areas by inundation with over 11% affected area while Quang Ngai Town inundated 8.1%. The study results will support decision makers in planning to reduce the impacts of natural disasters in Tra Khuc-Ve River basin in the future.